Characterization of reactive oxidized nitrogen in the global upper troposphere using recent and historic commercial and research aircraft campaigns and GEOS-Chem - N. Wei; E. A. Marais; G. Lu; G. Lu; R. G. Ryan; R. G. Ryan; B. Sauvage (Atmospheric Chemistry and Physics, 2025)
Reactive oxidized nitrogen (NOy) in the upper troposphere (UT) influences global climate, air quality, and tropospheric oxidants, but this understanding is limited by knowledge of the relative contributions of individual NOy components in this undersampled layer. Here, we use sporadic NASA DC-8 aircraft campaign observations, after screening for plumes and stratospheric influence, to characterize UT NOy composition and to evaluate current knowledge of UT NOy as simulated by the GEOS-Chem model. The use of DC-8 data follows confirmation that these intermittent data reproduce NOy seasonality from routine commercial aircraft observations (2003–2019), supporting the use of DC-8 data to characterize UT NOy. We find that peroxyacetyl nitrate (PAN) dominates UT NOy (30 %–64 % of NOy), followed by nitrogen oxides (NOx≡ NO + NO2) (6 %–18 %), peroxynitric acid (HNO4) (6 %–13 %), and nitric acid (HNO3) (7 %–11 %). Methyl peroxy nitrate (MPN) makes an outsized contribution to NOy (14 %–24 %) over the Southeast US relative to the other regions sampled (2 %–7 %). GEOS-Chem, sampled along DC-8 flights, exhibits much weaker seasonality than the DC-8, underestimating summer and spring NOy and overestimating winter and autumn NOy. The model consistently overestimates peroxypropionyl nitrate (PPN) by ∼ 10–16 pptv or 10 %–90 % and underestimates NO2 by 6–36 pptv or 31 %–65 %, as the model is missing PPN photolysis. A model underestimate in MPN of at least ∼ 50 pptv (13-fold) over the Southeast US results from uncertainties in processes that sustain MPN production as air ages. Our findings highlight that a greater understanding of UT NOy is critically needed to determine its role in the nitrogen cycle, air pollution, climate, and the abundance of oxidants.